Sapramiška - Pezdirc-Bartol, Mateja (Jezik in slovstvo, 2011)
Sapramiška, one of the most popular animal fairy tales by Svetlana Makarovič, was first published in 1976. Since then, it has had numerous reprints and has been included in all of the more extensive selections of the author's fairy tales. Sapramiška has been published in four different picture book publications, with illustrations by four different artists. It was first published as an audio play in 1986, and the same year was staged by the Ljubljana Puppet Theatre, where it has been staged continually until the present day. In 1978, Sapramiška had its first dramatic staging at SNG Nova Gorica, while its second staging took place in Kranj's Prešeren Theatre in 2000. The article analyses the representation of Sapramiška in various media, observing the interaction between various means of communication, i.e., the relationship between the verbal, the visual and the auditory, while at the same time outlining the work´s literary life of over a period of 35 years.
Keywords: Makarovič, Svetlana, 1939-; Slovene literature; slovenska književnost; slovenska otroška književnost; slovenske pisateljice; pravljice; umetne pravljice; živalske pravljice; Makarovič, Svetlana: Sapramiška; vizualni mediji; avdio mediji; lutkovne igre